Problematyka przesłanek odpowiedzialności z tytułu rękojmi za wady w języku teorii Grafów - automatyzacja rozstrzygania: [Problem of premises of liability by way of a guarantee for defects according to the theory of Graphs - automatization of solutions] (Studia Prawnicze / The Legal Studies, 1983)
The author analyses the problems of premises by way of a guarantee having applied the theory of graphs. The result of the analysis is an algorithm which enables to solve the problem of liability by way of a guarantee for an optional set of premises.In order to achieve the aim of the work a strict definition of a premise of liability by way of a guarantee is introduced. Then the typical, so-called unquestioned in the doctrine, premises of liability are considered. The premises are presented as a graph of premises which illustrates relationships resulting from the Civil Code. The premises of liability are thus systematized. Then the premises are compared in the so-called matrix of liability in order to find out which of the two premises is the decisive one. Owing to this comparison each premise is strictly defined with regard to other premises. On the basis of a graph of premises and matrix of liability, an algorithm is presented stating whether there occurs liability for a given set of premises or not. Then the considerations are repeated for all conditions which comply with the definition of the premise of liability. Thus not only typical premises are considered. At the end, a few interesting problems resulting from the above considerations are presented.